Metallic‐State SnS2 Nanosheets with Expanded Lattice Spacing for High‐Performance Sodium‐Ion Batteries. Issue 17 (25th July 2019) - Shi, Xiao; Chen, Shan‐Liang; Fan, Hai‐Ning; Chen, Xiao‐Hua; Yuan, Dingwang; Tang, Qunli; Hu, Aiping; Luo, Wen‐Bin; Liu, Hua‐Kun
Abstract: Metallic‐state 2D SnS2 nanosheets with expanded lattice spacing and a defect‐rich structure were synthesized by the intercalation of Ni into the van der Waals gap of SnS2 . The expanded lattice spacing efficiently enhanced the electrochemical performance of the SnS2 for sodium‐ion batteries owing to the change electron state density and energy band structure. In operando synchrotron XRD and theoretical calculations were used to gain insight into the influence of foreign metal‐ion doping and its location. The optimized architecture obtained by in situ uniform growth of nanosheets on carbon fibers significantly enhanced the electrochemical performance. The inherent advantages of this architecture are shorter paths for ion insertion and extraction, larger contact area for more sodium diffusion pathways, and superior electrolyte penetration. Benefiting from the Ni intercalated SnS2 bilayer, the internal adjustment of the electronic state and the enlarged interlayer spacing significantly enhanced the electron transport kinetics, which can be explained by the metallic‐state properties. The integrated electrode exhibited an initial high reversible capacity of 795 mAh g −1 at 0.1 A g −1, with a stable capacity retention of 666 mAh g −1 after 100 cycles. Good rate capability was also exhibited with specific capacities of 691, 564, 437 mAh g −1 at current densities of 200, 500, and 1000 mA g −1, respectively. Abstract : Bloating, but the good kind : Intercalation of Ni into SnS2 results in 2D nanosheets with expanded lattice spacing and a defect‐rich structure, resulting in a change in electron density and energy band structure. The resulting electrode structure, composed of vertically aligned nanosheets, exhibits shorter paths for ion insertion and extraction, larger contact area for more diffusion pathways, and superior electrolyte penetration.